Hydrogen peroxide metabolism and functions in plants. Issue 3 (13th October 2018) - Smirnoff, Nicholas; Arnaud, Dominique
Abstract : Contents   Summary 1197 I. Introduction 1198 II. Measurement and imaging of H2 O2 1198 III. H2 O2 and O2 ·− toxicity 1199 IV. Production of H2 O2 : enzymes and subcellular locations 1200 V. H2 O2 transport 1205 VI. Control of H2 O2 concentration: how and where? 1205 VII. Metabolic functions of H2 O2 1207 VIII. H2 O2 signalling 1207 IX. Where next? 1209   Acknowledgements 1209   References 1209 Summary: Hydrogen peroxide (H2 O2 ) is produced, via superoxide and superoxide dismutase, by electron transport in chloroplasts and mitochondria, plasma membrane NADPH oxidases, peroxisomal oxidases, type III peroxidases and other apoplastic oxidases. Intracellular transport is facilitated by aquaporins and H2 O2 is removed by catalase, peroxiredoxin, glutathione peroxidase‐like enzymes and ascorbate peroxidase, all of which have cell compartment‐specific isoforms. Apoplastic H2 O2 influences cell expansion, development and defence by its involvement in type III peroxidase‐mediated polymer cross‐linking, lignification and, possibly, cell expansion via H2 O2 ‐derived hydroxyl radicals. Excess H2 O2 triggers chloroplast and peroxisome autophagy and programmed cell death. The role of H2 O2 in signalling, for example during acclimation to stress and pathogen defence, has received much attention, but the signal transduction mechanisms are poorly defined. H2 O2 oxidizes specific cysteine residues of target proteins to the sulfenic acid form and, similar to other organisms, this modification could initiate thiol‐based redox relays and modify target enzymes, receptor kinases and transcription factors. Quantification of the sources and sinks of H2 O2 is being improved by the spatial and temporal resolution of genetically encoded H2 O2 sensors, such as HyPer and roGFP2‐Orp1. These H2 O2 sensors, combined with the detection of specific proteins modified by H2 O2, will allow a deeper understanding of its signalling roles.